Establishment of lung auscultation scoring method and responses of acute phase proteins and heat shock proteins in vaccinated and non-vaccinated goats - Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Yusuf, Abba; Muniandy, Kalai Vaani; Ahmad Tarmizi Tan, Ahmad Hafizin; Maslamany, Dharshini; Bitrus, Asinamai Athliamai; Mohd Lila, Mohd Azmi; Norsidin, Mohd Jefri (Tropical Animal Health and Production, 2019)
Pneumonic pasteurellosis is an economically important infectious disease in the small ruminant industry which causes sudden death and loss for farmers. Nonetheless, this disease is still a common sight in sheep and goats in Malaysia, probably due to the unpopular usage of pasteurellosis vaccine or inappropriate vaccination practices. The aim of this study was designed to classify the severity of pneumonia via the establishment of auscultation scoring method and to quantify the acute phase proteins and heat shock proteins responses from vaccinated and non-vaccinated goats. Goat farms, consist of vaccinated and non-vaccinated farms, were selected in this study: where 15 clinically normal healthy goats and 9 pneumonic goats were selected from vaccinated farms whereas 15 clinically normal healthy goats and 31 pneumonic goats from non-vaccinated farms were selected for this study. Crackle lung sounds were not detected in both vaccinated and non-vaccinated normal goats. However, vaccinated pneumonic goats showed mild crackle lung sound while non-vaccinated pneumonic goats exhibited moderate crackle lung sound. There were significant increases (p < 0.05) in acute phase proteins and heat shock proteins concentrations for the non-vaccinated pneumonic goats group. In this study, conclusion can be made that the vaccinated goats exhibited very mild clinical responses of pneumonia and non-significant biomarker responses compared to the non-vaccinated goats. Thus, vaccination is an effective preventive measure to control pneumonic pasteurellosis and acute phase proteins and heat shock proteins can be considered as future biomarkers in screening and rapid diagnostic method for this particular disease.